A multifunctional logic gate by means of a triple-chromophore fluorescent biothiol probe with diverse fluorescence signal patterns. Issue 98 (27th November 2017) - He, Longwei; Yang, Xueling; Xu, Kaixin; Yang, Yunzhen; Lin, Weiying
Abstract : Multiple logic gates such as OR, TRANSFER, INH, NOT, and YES operations were achieved on a single triple-chromophore fluorescent probe by using biothiols and fluorescence signal patterns as the multiple inputs and outputs. Abstract : A novel multifunctional logic gate based on a triple-chromophore (coumarin–NBD–flavylium, CNF) fluorescent biothiol probe with diverse fluorescence signal patterns was rationally designed and synthetized. On the new triad CNF, diverse logic operations such as OR, TRANSFER, INH, NOT, and YES logic gates were achieved by using biothiols and fluorescence signal patterns as the multiple inputs and outputs, respectively.